Ensuring Competitive Advantage through Innovation Capability and Clustering in the Thai Automotive Parts Molding Industry: A SEM Approach - Sirorath Tiengtavaj; Thepparat Phimonsathienand; Wanno Fongsuwan (My University, 2017)
Abstract Thailand hosts over 50 percent of the world’s top OEM automotive parts suppliers and additionally is home to over 2,400 Tier 1-3 manufacturers and suppliers. Given the significance of these numbers and Thailand’s leading ranking and contribution to the global automotive industry, research was undertaken to determine how manufacturing clusters and innovation capability effect competitive advantage as it relates to automotive production part management. Multiple objectives were established which included the study of the effects and overall influences of the various variables on competitive advantage as well as the development of a structural equation model (SEM) to define how innovation and manufacturing clustering affects the competitive advantage within the Thai automotive parts molding sector. Quantitative methods analysis was conducted on the data from 240 automotive production and components suppliers’ questionnaires collected from industry managers with the research results partially obtained from the analysis by use of (PLS)-graph. Qualitative research was also obtained by use of purposive sampling from in-depth interviews from ten senior managers. The results obtained indicated that clusters and innovation capability has a significant and positive effect on competitive advantage. Thus, the findings from the research illustrate that if an organization focuses on clusters, there will be a knock-on effect within the automotive parts groups leading to the increase in innovation capability, which creates a greater competitive advantage, not only for the enterprises, but also for Thai society as well.
Keywords: Original equipment manufacturer; Quality and Supply Management